Effectiveness of Type M1 AMF Inoculum and Host Plant Species on the Growth of Sandalwood (Santalum album Linn.) Seedlings - Finmeta, Abdonia; Taneo, Davik Eliaser; Bunyani, Nur Aini; Kerihi, Eka Citra.G. (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The successful establishment of sandalwood (Santalum album L.) in the degraded dry savanna of East Nusa Tenggara, Indonesia, remains limited because young seedlings often fail to adapt to marginal soil conditions and seasonal water scarcity. This study evaluated the effects of Arbuscular Mycorrhizal Fungi (AMF) inoculum (type M1) and different host plant species on the growth of sandalwood seedlings during the nursery stage. The experiment employed a completely randomized split-plot design with two AMF treatments (without AMF and AMF type M1) and four host plant treatments (without host, chili, mung bean, and Leucaena). Growth performance was assessed based on plant height, stem diameter, and leaf number. The results showed that both AMF inoculation and host plant species significantly affected all measured growth parameters. The combination of AMF type M1 and mung bean as the host plant produced the highest growth, with plant height of 14.09 cm, stem diameter of 2.26 mm, and 19.20 leaves per seedling. These findings indicate that the symbiotic association between AMF and an appropriate host plant enhances nutrient and water uptake, thereby supporting seedling growth under nursery conditions. The study demonstrates that integrating AMF type M1 with mung bean as a host plant is a promising strategy to improve sandalwood seedling quality and may contribute to more successful establishment in dryland restoration and reforestation programs.